Pengaruh Jumlah Peserta Dana Pensiun Syariah terhadap Imbal Hasil dengan Peran Mediasi Strategi Kinerja Keuangan dan Pertumbuhan Investasi - Ihksan, Abdullah Khairul; Syamlan, Yaser Taufik (Ekonomis: Journal of Economics and Business, 2025)
This study aims to analyze the effect of the number of participants in Islamic pension funds on returns, with the mediation of financial performance strategies and investment growth. The study population includes all Islamic pension funds registered with the Islamic Non-Bank Financial Industry (IKNB) of the Financial Services Authority (OJK) during the 2018-2023 period. The analysis technique used is SEM-PLS. The results show that the number of participants in Islamic pension funds influences returns through the mediation of financial performance and investment growth.